Exploring PERMA in spectator sport: Applying positive psychology to examine the individual-level benefits of sport consumption. Issue 5 (November 2016) - Doyle, Jason P.; Filo, Kevin; Lock, Daniel; Funk, Daniel C.; McDonald, Heath
Highlights: We focus on examining the benefits of spectating from the individual's perspective. Positive psychology and the PERMA framework are applied to spectator sport. We reveal how positive emotions, relationships, meaning and accomplishment are activated during the season, and in the off-season. Managerial actions focus on fostering the relationships derived through spectating. Abstract: Sport spectating provides numerous benefits for sport organisations and individuals. In this paper we use a positive psychology approach to examine the individual-level benefits of sport consumption in order to investigate the activation of five domains of well-being: positive emotions, engagement, relationships, meaning, and accomplishment (PERMA). Using a two-study panel research design, we collected qualitative data from a sample of Australian Rules Football consumers. In the first study, we explored how the PERMA domains were activated during the season. Study two included a follow-up interview with eight initial respondents in the off-season. We found evidence of four PERMA domains that were activated in the sport spectator context by a variety of consumer experiences. The emergence of these domains in both studies suggests sport marketers would benefit from actions including: creating more social spaces within their stadiums, hosting regular off-season events, and creating social-media based competitions which promote fan engagement and interactions throughout the calendar year.